2021
DOI: 10.1111/bjd.20786
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world effectiveness of brentuximab vedotin in the treatment of CD30‐positive cutaneous T‐cell lymphoma: a single‐centre retrospective review

Abstract: of nutrients and oxygenation. It amplifies the migration of epithelial cells from the surrounding skin and thereby augments fibroblastic growth and epithelialization. 5,7,8 These factors in turn may help to counteract the clinicopathological basis of venous stasis.A literature search did not reveal any relevant data on the use of citric acid for patients with eczema. To the best of our knowledge, this is the first report where citric acid was used for the treatment of infected venous eczema with a positive out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…In addition, we observed a high rate of CR in patients with FMF (Figure 2a–d), a variant of MF that due to the deep location of the infiltrate, is considered particularly resistant to skin‐directed therapies. Although in the ALCANZA trial, no specific information about this MF variant was given, 1 our results agree with recent observations and suggest that BV may be an effective option in FMF 9,14 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, we observed a high rate of CR in patients with FMF (Figure 2a–d), a variant of MF that due to the deep location of the infiltrate, is considered particularly resistant to skin‐directed therapies. Although in the ALCANZA trial, no specific information about this MF variant was given, 1 our results agree with recent observations and suggest that BV may be an effective option in FMF 9,14 …”
Section: Discussionsupporting
confidence: 89%
“…Although in the ALCANZA trial, no specific information about this MF variant was given, 1 our results agree with recent observations and suggest that BV may be an effective option in FMF. 9,14 Looking at the CD30 LPD, in this study we included 10 pcALCL and 2 LyP. Eight of the 10 pcALCL patients had advanced stages with extracutaneous involvement.…”
Section: Discussionmentioning
confidence: 99%
“…2a-d), a variant of MF that due to the deep location of the infiltrate, is considered particularly resistant to skin-directed therapies. Although in the ALCANZA trial no specific information about this MF variant was given 1 , our results agree with recent observations and suggest that BV may be an effective option in FMF 9,14 .…”
Section: Discussionsupporting
confidence: 91%
“…Real-world studies on brentuximab vedotin therapy for CTCL support the results of the ALCANZA trial, with good responses to treatment observed in patients with MF and C-ALCL [ 94 98 ] and provide evidence for potential benefits of brentuximab vedotin in other CTCL subtypes [ 94 , 98 101 ]. A European retrospective study in patients with MF and SS did not detect any differences in response by CD30 level or previous treatment, but suggested a potential association between lower disease stage and higher ORR4, as well as between LCT and skin ORR [ 96 ].…”
Section: Real-world Data On Brentuximab Vedotin In Ctclmentioning
confidence: 68%
“…The aforementioned European study in patients with MF and SS did not detect any difference in treatment response between these two subtypes, suggesting that patients with SS can benefit from brentuximab vedotin treatment to a similar extent as MF patients [ 96 ]. Cases studies in patients with refractory primary cutaneous gamma-delta T-cell lymphoma have also noted benefits of brentuximab vedotin treatment [ 100 , 101 ], and some retrospective studies of brentuximab vedotin for CTCL have included a range of different rare subtypes, noting treatment responses in folliculotropic MF, SS with LCT, and granulomatous MF [ 94 , 98 ].…”
Section: Real-world Data On Brentuximab Vedotin In Ctclmentioning
confidence: 99%